Transformers. The last knight [videorecording (Blu-Ray)] - Wahlberg, Mark, 1971-; Duhamel, Josh, 1972-; Tucci, Stanley; Hopkins, Anthony, 1937-; Haddock, Laura, 1985-; Turturro, John, 1957- (Paramount Pictures, 2017)
Humans and Transformers are at war, Optimus Prime is gone. The key to saving humanity's future lies buried in the secrets of the past, in the hidden history of Transformers on Earth.